Ghosted at Work : The Ripple Effect of Ostracism on Millennials’ Performance in India’s Food Sector - Yadav, Sarika; Joshi, Meha; Bugalia, Poorva; Lamba, Nischay (Prabandhan: Indian Journal of Management, 2025)
Purpose : Social interactions and conducive work environments play a crucial role in enhancing employee productivity and performance. Hostility in the workplace environment can emanate from low morale and be counterproductive to the health of the organization. Therefore, it is imperative to examine workplace ostracism in this era to gain traction. This study examined the relationship between workplace ostracism and job performance. This study also gauged the role of job satisfaction in the nexus between workplace ostracism and job performance among 300 million employees in the food processing industry in India. Methodology : This study explored the associations between workplace ostracism, job performance, and job satisfaction. The sample population consisted of 300 working professionals in the food processing industries in different states of India. To ensure the non-occurrence of social desirability bias, confidentiality of the researchers was maintained, and due attention was paid to maintaining anonymity (Podsakoff et al., 2003). Findings : The results showed that job satisfaction was severely impacted by workplace ostracism, and thus, decreased employees’ job performance. Practical Implications : This study has several implications for managers. First, ostracism behavior should be monitored and identified. If a victim displays adverse workplace ostracism, managers should intervene and help them cope. Additionally, managers should maintain good relationships with subordinates and try to avoid the act of ostracism as other employees may be encouraged to act similarly. Originality : The study is original because it focuses on the food processing industry, a sector that has not been touched upon by researchers.